Homotopy extension property in homotopy theory for topological semigroups. - Kilicman, Adem; Saif, Amin (Hindawi Publishing Corporation, 2012)
The purpose of this paper is to extend the concept of homotopy extension property in homotopy theory for topological spaces to its analogical structure in homotopy theory for topological semigroups. In this extension, we also give some results concerning on absolutely retract and its properties.